2014
DOI: 10.1177/0956797614549209
|View full text |Cite
|
Sign up to set email alerts
|

Social-Network Complexity in Humans Is Associated With the Neural Response to Social Information

Abstract: Humans have evolved to thrive in large and complex social groups, and it is likely that this increase in group complexity has come with a greater need to decode and respond to complex and uncertain communicatory signals. In this functional MRI study, we examined whether complexity of social networks in humans is related to the functioning of brain regions key to the perception of basic, nonverbal social stimuli. Greater activation to biological than to scrambled motion in the right posterior superior temporal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 29 publications
3
31
0
Order By: Relevance
“…In addition, some diseases, such as autism spectrum disorders (ASD) (Alaerts et al, 2014;von dem Hagen et al, 2011), simultanagnosia (Sakurai, Hamada, Tsugawa, & Sugimoto, 2016), and conduction aphasia (Hickok, 2009), are highly related to lesions in the pSTS. Therefore, these converging results suggest that the pSTS is functionally complex, is related to multiple information processing circuits (Abrams et al, 2013;Dziura & Thompson, 2014), and is involved in several brain diseases (Redcay, 2008;Vallesi, 2016;Yang, Rosenblau, Keifer, & Pelphrey, 2015). These findings may, therefore, imply that the pSTS consists of more than one functional subregion, which contribute to a variety of functional processes.…”
mentioning
confidence: 93%
“…In addition, some diseases, such as autism spectrum disorders (ASD) (Alaerts et al, 2014;von dem Hagen et al, 2011), simultanagnosia (Sakurai, Hamada, Tsugawa, & Sugimoto, 2016), and conduction aphasia (Hickok, 2009), are highly related to lesions in the pSTS. Therefore, these converging results suggest that the pSTS is functionally complex, is related to multiple information processing circuits (Abrams et al, 2013;Dziura & Thompson, 2014), and is involved in several brain diseases (Redcay, 2008;Vallesi, 2016;Yang, Rosenblau, Keifer, & Pelphrey, 2015). These findings may, therefore, imply that the pSTS consists of more than one functional subregion, which contribute to a variety of functional processes.…”
mentioning
confidence: 93%
“…It is possible that the pSTS serves as a high-level visual processor that is not central to the processing of social meaning from such stimuli. The selectivity of the fMRI response of the pSTS region to biological motion region does appear to be linked to social abilities (Pelphrey, Morris, & McCarthy, 2004;Saxe, Xiao, Kovacs, Perrett, & Kanwisher, 2004), and even the size and complexity of social networks (Dziura & Thompson, 2014), suggesting a more diffuse role in social cognition. More recently, an fMRI study showed that the pSTS region is involved in the processing of emotion conveyed by body movements (Goldberg, Christensen, Flash, Giese, & Malach, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…To ensure accurate targeting of rpSTS for the cTBS, we first collected blood oxygen level-dependent (BOLD) fMRI data as participants viewed a block design paradigm, consisting of five blocks of scrambled and intact 12-dot PLDs (Dziura & Thompson, 2014). All stimuli were obtained from the Carnegie Mellon University Graphics Lab Motion Capture Database functionally-localized rpSTS and vertex, (as used by Pitcher et al (2008), the midway point between the nasion and the inion, equidistant from the left and right intertragal notches).…”
Section: Fmri Localizer: Identification Of Rpsts Target Site Fmri Datmentioning
confidence: 99%
See 1 more Smart Citation
“…Some individuals have 115 more social skills than others, which could in part be influenced by how well they learn from the 116 social world around them (Heerey, 2013;Milch-Reich, Campbell, Pelham, Connelly, and Geva, 117 1999). Sociality is also linked to both neural and behavioral measures of social perception 118 (Baron-Cohen et al, 1999;Bickart, et al, 2011;Dziura and Thompson, 2014;Kanai et al, 2011). 119…”
mentioning
confidence: 99%